Pemasaran Ikan Tuna (Thunnus sp) di Pelabuhan Perikanan Nusantara (PPN) Kota Ternate - Azis Husen (Yayasan Literasi Sains Indonesia, 2022)
The Ternate Archipelago Fishery has a strategic role in development of fisheries and marine affairs, namely as a center for marine fisheries activities.A properly functioning Nusantara Ternate Fishery will be a beneficial point between economic marketing activities at sea and economic marketing activities on land.The purpose of this research is to know the marketing management method of tuna fish at the Ternate Archipelago Fisheries.This research was conducted at the Ternate Archipelago Fishery in Bastiong Village, South Ternate City. The method of data collection was using secondary and primary data.Marketing of tuna exports was 621,951 (kg), in 2018 tuna exports were 540,450 (kg), in 2019 the number of tuna exports was 268,384 (kg), in 2020 tuna exports were 447,550 (kg) and in 2021 PPN Ternate carried out exports 589,767 (kg). Marketing exports of tuna from Ternate, North Maluku directly to Singapore, Vietnam while the aims of export destinations are Bitung, Makassar, Surabaya, Jakarta and Batam. The activity of the fishing business industry is increasing because during the Covid-19 pandemic in 2019-2020 tuna exports experienced a very significant decline.The marketing of tuna for PPN Ternate nationally and internationally is very promising for development, so the marketing strategy is needed to be implemented, including improving facilities and infrastructure, making technological efforts for the fishing boat and fishing gear.